Translation Ideology: An Analysis of Cultural Words in “Educated” Memoir by Tara Westover - Munawaroh, Syarifah Robiatul; Andriani, Zulfi Zumala Dwi (JL3T (Journal of Linguistics, Literature and Language Teaching), 2024)
This study aims to describe translation ideology in translating cultural words of the “Educated” memoir by Tara Westover. The research method is descriptive qualitative. The data taken are in the form of words or phrases related to cultural words in “Part One” of “Educated” by Tara Westover and its translation. This article analysed the theories of cultural categories by Newmark (1988), translation methods by Molina & Albir (2002), and translation ideology by Venuti (1995) . The research finding demonstrates four categories of cultural words in the memoir, such as ecology, material culture (artifact), social culture, and organization, custom and ideas. Furthermore, translation techniques applied by the translator were borrowing, amplification, description, adaptation, literal translation, established equivalent, and calque. The findings of this research show that the most dominant technique used in this memoir is borrowing (64%). In terms of translation idelogy, the findings of this study indicate that foreignization is more prevalent than domestication. The research result can provide insights to EFL learners, especially in translation materials, to be more careful in translating cultural words because of the cultural barriers between the SL and TL. Moreover, this study contributes to developing cultural and linguistic studies by exploring domestication and foreignization ideologies in translating English literary works into Indonesian.